WEBSITE DESIGN AND INSTALLATION OF INFORMATION ADVERTISING PROPERTY Up TO DATE 4.0 USING PHP AND MYSQL DATABASE - Hardy Edhi Swasono; Drs. Soebijantoro, MMEng Drs. Soebijantoro, MMEng (Jurnal Sistem Informasi, 2002)
Provides information about a product, object or goods offered to consumers is animportant matter, especially concerning information to the property that does notdisplay brand. Provide information via the internet is one of the solutions from theworld of e-commerce is booming lately. In addition to its affordable cost is also aglobal and fast.The program e-commerce website is an information service about object / itemconsists of two main pages are pages and pages to users for the system ofadministration that can be updated at any time during 24 hours.